Implementasi Pembelajaran Kooperatif Pada Materi Bahasa Arab di Pondok Pesantren Al Istiqomah Kebumen - Imam Satibi; Muna Fauziah (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2020)
The purpose of this study is to analyze the management of cooperative learning at Al Istiqomah Kebumen Islamic Boarding School. This research is a qualitative research. Data obtained from observation and in-depth interviews. The research was conducted at the Al Istiqomah Islamic Boarding School, Tanjungsari, Petanahan, Kebumen. The subjects of this study were course participants or customers of the Kebumen Arab Village. Data were analyzed through interactive analysis. The sequence of stages are data collection, data reduction, data presentation, and drawing conclusions. The research found that the implementation of cooperative learning in the Kebumen Arab Village had gone well by emphasizing the participants to speak with the concept of biʻah lughawiyah or the Arabic language environment and the direct method of aṭ-Ṭarῑqah al-Mubāsyarah which was combined with cultural and sociolinguistic elements so that they were able to adapt to speak Arabic.